The teaching of self-care to ostomy patients and their families: an integrative review - Nariman de Felício Bortucan Lenza; Helena Megumi Sonobe; Luciana Scatralhe Buetto; Marco Gimenes dos Santos; Mariza Silva de Lima (Universidade de Fortaleza, 2013)
Objectives: To characterize the national and international literature on the teaching of selfcare to bowel ostomates and their relatives. Methods: It is an integrative review, in LILACS and MEDLINE electronic databases, in the period from 1996 to 2006, with the keywords 'teaching', 'ostomates' and 'nursing'. Results: The sample was composed of eight articles, which reported the importance of teaching strategies applied with patients and their families regarding self-care and management of the stoma and collectors, however, no study has brought specific and systematized teaching strategies. Conclusion: The analyzed literature has demonstrated the importance of teaching strategies addressing the issue of self-care for the ostomates, but expressed the lack of researches and publications on the implementation of contextualized actions and with appropriate language for these patients and their families.